ARSITEKTUR UMA LULIK FUILORO, LOSPALOS KOTA, TIMOR-LESTE - maria immaculata ririk winandari; Andre Mariano Dos Santos Belo (architecture department, Engineering faculty, Universitas Diponegoro, 2021)
Uma Lulik is a sacred house for the people of Timor-Leste. This house is the unification of Nain (owner, ruler or supreme), Beala (ancestor), Lulik (sacred